SEJARAH RUMAH SINGGAH SULTAN SIAK DI KOTA PEKANBARU TAHUN 1928 - Rafsanjany, Dudy Akbar; Isjoni, Isjoni; Kamaruddin, Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Sultan Siak Shelter House is a house built by H. Nurdin Putih in 1895 and later occupied by H. Zakaria bin H. Abdul Muttalib or better known as Mr. Qadhi Zakaria. Mr. Qadhi Zakaria is a leader of Sharia Law in Siak kingdom located in Siak Sri Indrapura, Tuan Qadhi Zakaria has a house located on the banks of Siak River in Senapelan area. When Sultan Sharif Kasyim II visited Pekanbaru, Mr. Qadhi's house was made a resting place by the Sultan and his guards. This house is also used as a gathering place and a meeting place by the Sultan and the scholars who are in Senapelan. Tuan Qadhi's house was first renovated in 1928, the material used as a replacement for the old part of the house in came from Singapore, the renovation of the house was done after the arrival of Sultan Syarif Kasyim II to Pekanbaru. Aside from being a stopover for Sultan Sharif Kasym II, Tuan Qadhi's house is also used in religious, social and political activities, this house was once occupied and then made headquarters by the Dutch army in 1939. Furthermore the home of Mr. Qadhi was re-occupied by Mr. Qadhi's family until the year 1994, but Mr. Qadhi's family decided to sell the house and move to a new home, where Mr. Qadhi's house was bought by an old iron entrepreneur named Atan Gope. In 2010 this house began in the conservation and purchased by the city government Pekanbaru, because the house has a long history and a considerable role for the Sultan and the kingdom of Siak. The renovation is done back to this house in 2012, now this house has been used as a cultural heritage site and around the house built park for family recreation. And directly managed by the Department of Tourism and Culture of Pekanbaru city.Keywords: History, Shelter House, Sultan Siak, Pekanbaru